Ileal tuberculosis diagnosed in preventive colonoscopy: Case report describing endoscopic aspects, treatment and healing (Research, Society and Development, 2024)
The authors' objective in presenting this case is to emphasize the importance of routine ileal intubation during colonoscopy, describe a rare case of isolated ileal tuberculosis in an asymptomatic patient, and discuss the challenge of achieving a correct etiological diagnosis when faced with atypical ileal lesions. In the described case, during a colonoscopy for colorectal cancer screening in an asymptomatic patient, ileal intubation enabled the detection of an atypical ulcerated lesion. Further investigation through biopsies, acid-fast bacilli (AFB) testing, and serological tests led to the diagnosis of isolated ileal tuberculosis. The patient underwent medical treatment, and a subsequent ileocolonoscopy confirmed healing. Although intestinal tuberculosis is relatively rare (1-3% of total tuberculosis cases), it should always be considered when ulcerated lesions are detected in the ileal region, especially in developing countries. Physicians must be vigilant and capable of recognizing and differentiating it from other conditions, as a misdiagnosis and subsequent incorrect treatment could pose serious harm to the patient. The case described illustrates the benefits of routine ileal intubation as a strong argument for the quality criteria of the examination.